Analisis Sifat Fisik Dan Mekanik Kayu Kelapa Sawit Hasil Kompregnasi Melamine Formaldehyde - Bambang Arif Hidayat; Alfian Kamaldi; Fakhri Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
During the past time the utilization of palm oil tree only limited to producing fruit to produce oil with all their derivatives, as well as the utilization of husk and midrib. Stem, as the biggest mass palm oil tree has not been used commercially due to its lack of quality. One effort in improving quality of palm oil wood is compregnation. Compregnation interpreted as an effort of putting the chemicals into wood structure using prresure. Chemicals that can penetrate into wood structure in this case is melamine formaldehyde resin. The result of research showed that compregnation palm oil wood by melamine formaldehyde increased the specific of gravity of wood from 0,32 before compregnation to 0,48, 0,58 and 0,65 for 50%, 75% and 100% concentrate. Moisture content decreased from 12,05% before compregnation to 10,67 at 100% concentrate. MOR increased from 64,58 kg/cm2 before compregnation to 131,54 kg/cm2, 188,94 kg/cm2 and 361,14 kg/cm2 each for 50%, 75% and 100% concentrate. Keyword: Elaeis guineensis Jacq, Compregnation, Melamine Formaldehyde, MOR